Oceanus: A multi-spacecraft flagship mission concept to explore Saturn and Uranus. Issue 9 (1st May 2017) - Mansell, J.; Kolencherry, N.; Hughes, K.; Arora, A.; Chye, H.S.; Coleman, K.; Elliott, J.; Fulton, S.; Hobar, N.; Libben, B.; Lu, Y.; Millane, J.; et al.
Abstract: Uranus, together with Neptune in our Solar System, belongs to a class of planets called ice giants, which have never been explored using a dedicated mission. A mission to explore the ice giants is one of the highest priority missions of NASA. In this paper, we present a new and unique multi-probe, multi-planet spacecraft to explore two of the outer planets, Saturn and Uranus. The mission concept addresses the high-priority science goals of Saturn and Uranus as set forth by the National Research Council's Planetary Sciences Decadal Survey: Visions and Voyages for Planetary Science in the Decade 2013–2022. The growing importance of understanding the evolution and role of ice giants in extra-solar planetary systems makes Uranus a pertinent scientific target. The mission concept employs the Space Launch System to deliver a 1700 kg orbiter to Uranus using a ballistic Saturn-Uranus trajectory with a time-of-flight of 11.5 years. The baseline mission concept includes two atmospheric entry probes: one deployed at Saturn and another at Uranus prior to an impulsive orbit capture. A payload of nine remote sensing and in situ plasma instruments onboard the orbiter support a broad array of investigations during the nominal 2-year science mission. In addition to the baseline concept, system trade studies were conducted to explore the advantages of aerocapture and use of the Space Launch System. Based on the results of these trade studies, a preferred point design within constraints of NASA's Flagship program can be launched in the late 2020s. A neural network model using analogy-based data was developed to estimate the mission cost, which was found to be $1.9 billion in FY15$.